2014
DOI: 10.4209/aaqr.2013.05.0180
|View full text |Cite
|
Sign up to set email alerts
|

Methane Generation from the Intestine of Muscovy Ducks, Mule Ducks and White Roman Geese

Abstract: Livestock are one of the largest single sources of methane emissions, which is a greenhouse gas. In this study, alfalfa meal was tested as a feed additive to lower the methane generation in the three species of waterfowl. Four experiments were conducted to determine methane generation in the intestines of Muscovy ducks, mule ducks and White Roman geese of the same age and with the same diet. In experiment I, the in vitro methane generation of the cecal contents was the largest compared to other intestinal comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…In contrast, nitrous oxide emission from geese is not influenced by cecectomy (Chen et al, 2003) ( Table 5). Addition of alfalfa can reduce methane production by over 70% in Muscovy ducks, mule ducks and white Roman geese (Chen et al, 2014). Interestingly, there was no overall effect of addition of antibiotics to feed on VFA production by chickens (Kumar et al, 2018).…”
Section: Cecamentioning
confidence: 97%
“…In contrast, nitrous oxide emission from geese is not influenced by cecectomy (Chen et al, 2003) ( Table 5). Addition of alfalfa can reduce methane production by over 70% in Muscovy ducks, mule ducks and white Roman geese (Chen et al, 2014). Interestingly, there was no overall effect of addition of antibiotics to feed on VFA production by chickens (Kumar et al, 2018).…”
Section: Cecamentioning
confidence: 97%
“…Additionally, CH 4 production from manure produced in the livestock and poultry industries is a major GHG source (Yang et al, 2003;Zhou et al, 2007;Wang et al, 2017). Geese ceca are major places for in vivo CH 4 production (Chen et al, 2009;Chen et al, 2014). Chen et al (2003) showed CH 4 production from caecectomized geese was only 8 -10% of that of sham-operated geese.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients of cecal contents in poultry can be fermented and converted into short-chain (2 -5 carbons) fatty acids and biogas (e.g. ammonia, carbon dioxide and CH 4 ) by microorganisms (Marounek et al, 1999;Chen et al, 2014). Besides, microorganisms cultured from poultry and cattle can generate CH 4 (Van Kessel & Russell, 1996;Montagna et al, 2019), suggesting that microorganisms in poultry ceca and bovine rumen fluids have similar functions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations